Penerapan Standar Akuntansi Keuangan EMKM dalam Penyusunan Laporan Keuangan Pada Usaha Kerajinan Sangkar Burung Desa Sukowono Kabupaten Jember - Wahdaniah, Iklimatul; Lestari, Hari Budi; Epriliyana, Nike Norma (ACCOUNT (Journal of Accounting and Finance), 2023)
Financial Accounting Standards for Micro, Small and Medium Entities are accounting standards intended for Micro, Small and Medium Enterprises where with the existence of Standards for Micro, Small and Medium Entities it is hoped that Micro, Small and Medium Enterprises will be more independent and more advanced and Micro, Small and Medium Enterprises can record their business financial reports, improve information Accounting has an important role in achieving business success. This research aims to explain the implementation of Standards for Micro, Small and Medium Entities financial accounting standards in preparing financial reports for the Bird Cage Craft Business in Sukowono Village, Jember Regency. The method used in this research is Qualitative Descriptive. The results of the research show that the preparation of financial reports for the Bird Cage Craft Business in Sukowono Village, Jember Regency has gone well and is in accordance with Standards for Micro, Small and Medium Entities. This can be seen from the research results where these Micro, Small and Medium Enterprises apply financial reports including profit and loss reports, capital requirements, financial position reports, as well as notes to financial reports.